Why should America support Ukraine? - Nataliya Gorodnia (Американська історія і політика, 2016)
The paper reveals principal factors of the U.S. support of Ukraine during Russia’s aggression and the place of Ukraine in the system of the U.S. national interests. The author argues that before Russia’s aggression Washington prioritized relations with Russia to other post-Soviet nations, including Ukraine. The U.S. interests to Ukraine before the crisis, besides its nuclear disarmament, were caused mainly by geopolitical calculations. Because of Ukraine’s strategic location between Russia and Europe, developments in Ukrainian-Russian relations indicated trends in Russia’s policy and the prospects of its interactions with Europe.